PENGARUH OPINI AUDIT, FINANCIAL DISTRESS, DAN PERGANTIAN MANAJEMEN TERHADAP ROTASI AUDITOR - Olivia Ananda Agita; Retna Sari (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
This research purpose to find out empirically the effect of audit opinion, financial distress, and management change on auditors rotation in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020. This research is a type of quantitative research that uses secondary data from company reports. This study used a sample of 177 companies. Hypothesis testing in this study uses Logistics Regression Analysis using the SPSS (Statistical Product and Service Solution) version 25 program and a significance level of 5% (0.05). The results of data analysis show that audit opinion, financial distress, and management change have no effect on auditor rotation.Keywords: Audit Opinion, Financial Distress, Management Turnover, Auditor Rotation